Severe left atrial enlargement due to carfilzomib use in multiple myeloma. (December 2019) - Dasanu, Constantin A; Plaxe, Steven C; Popescu, Iliana M; Gupta, Varun; Sontz, Eric; Codreanu, Ion
Several cardiovascular effects have been attributed to carfilzomib in the recent literature. These side effects must be recognized promptly by treating physicians and pharmacists. Special attention is required in patients with pre-existing cardiac conditions, liver function abnormalities and/or advanced age. This is the first report of a severe left atrial enlargement due to carfilzomib use in the setting of multiple myeloma. This condition improved dramatically seven months after cessation of carfilzomib. The authors discuss further various cardiac and vascular abnormalities linked with carfilzomib in the medical literature. Prompt withdrawal of this agent is essential in these cases as it may prevent dismal outcomes.